136k views
3 votes
Which expression is equivalent to The equation

Which expression is equivalent to The equation-example-1
User Pitazzo
by
5.6k points

2 Answers

3 votes

Answer:

The correct answer is last option 1/x²⁴

Explanation:

Points to remember

1). (x)⁻ᵃ = 1/xᵃ

2). (xᵃ)ᵇ = xᵃᵇ

3). xᵃ/xᵇ = xᵃ⁻ᵇ

It is given that, { x⁻⁶/x² }³

To find the equivalent expression

{ x⁻⁶/x² }³ = (x⁻⁶ ⁻ ²)³

= (x⁻⁸)³

= x⁻²⁴

= 1/x²⁴

Therefore the correct answer is last option

{ x⁻⁶/x² }³ = 1/x²⁴

User Arto Bendiken
by
5.8k points
1 vote

Answer: last option.

Explanation:

The negative exponent rules establishes the following:


a^(-n)=(1)/(a^n)

The power to power property establishes:


(a^b)^c=a^(bc)

The product of powers property establishes that when you multiply two powers with equal base you must add the exponents.

Applying the properties, you obtain the equivalent expression shown below:


((1)/(x^2*x^6))^3=((1)/(x^8))^3=(1)/(x^(24))

Therefore the answer is the last option.

User Oleg Shleif
by
6.0k points